Migration of nitrite corrosion inhibitor in calcium silicate hydrate nanopore: A molecular dynamics simulation study - Hu, Xiaoxia; Zheng, Heping; Tao, Rui; Wang, Pan (Frontiers in Materials, 2022)
Nitrite is an effective corrosion inhibitor that can inhibit the corrosion of steel reinforcement and extend the service life of reinforced concrete. The transport speed of nitrite in the cement micro-porous channels determines the anti-corrosion effect of reinforcing steel. In this paper, the transport behavior of three nitrite corrosion inhibitors, namely LiNO2, Ca(NO2)2, and NaNO2, in cement micro-porous channels is investigated based on molecular dynamics simulations and finds that NO2- in LiNO2 has the fastest transport speed in the channels. The ions’ local structure and dynamic behavior of ions analysis reveal that ion clusters and pores adsorption determine the speed of ion transport. Compared with the other two nitrites, the Li ions have the weakest ability to capture NO2- and form the most unstable clusters (NO2--Li-water) in the LiNO2 solution. Meanwhile, the coordination numbers results indicate that water in LiNO2 provides the most potent driving force. These phenomena reasonably explain the fastest transport speed of NO2- through the pores in LiNO2 solution. The transport behavior of corrosion inhibitors in the micro-porous channels is thoroughly decoded at the atomic level, which is instrumental in solving the problem of the optimal corrosion inhibitor selecting for the design of highly durable concrete.